2012
DOI: 10.1111/jnc.12082
|View full text |Cite
|
Sign up to set email alerts
|

Vinpocetine and α‐tocopherol prevent the increase in DA and oxidative stress induced by 3‐NPA in striatum isolated nerve endings

Abstract: Vinpocetine is a neuroprotective drug that exerts beneficial effects on neurological symptoms and cerebrovascular disease. 3-nitropropionic acid (3-NPA) is a toxin that irreversibly inhibits succinate dehydrogenase, the mitochondrial enzyme that acts in the electron transport chain at complex II. In previous studies in striatum-isolated nerve endings (synaptosomes), we found that vinpocetine decreased dopamine (DA) at expense of its main metabolite 3,4-dihydroxyphenylacetic acid (DOPAC), and that 3-NPA increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 22 publications
2
8
0
1
Order By: Relevance
“…NPA administration caused robust oxidative stress as evidenced by elevated oxidative markers in both cytosol and mitochondria of brain regions. These results are in agreement with previous findings among NPA models of neurotoxicity [9,38]. Evidence in experimental animals has clearly shown that NPA affects different brain regions, and striatal neurons were more vulnerable [39].…”
Section: Discussionsupporting
confidence: 93%
“…NPA administration caused robust oxidative stress as evidenced by elevated oxidative markers in both cytosol and mitochondria of brain regions. These results are in agreement with previous findings among NPA models of neurotoxicity [9,38]. Evidence in experimental animals has clearly shown that NPA affects different brain regions, and striatal neurons were more vulnerable [39].…”
Section: Discussionsupporting
confidence: 93%
“…These results are in harmony with other results which found that vinpo inhibits carrageenan-induced peripheral decrease in antioxidant capacity level [46]. This can be attributed to its powerful antioxidant activities and ability to reduce oxidative stress and ROS [58]. It is worthy to note that, combination of vinpo with indo at either dose levels resulted in more significant increase in serum TAC levels.…”
Section: Photomicrographs Of Brain Tissue Sections Stained By Hematoxsupporting
confidence: 89%
“…Consistently, various natural compounds such as curcumin from turmeric and polyphenols present in blueberries, strawberries, green tea, black tea, grapes, and red wine have displayed neuroprotective effects in both in vivo and in vitro models through antioxidant activity (Mancuso et al, ). In this context, a close relationship between antioxidation and neuroprotection has frequently been demonstrated in several neuroprotective conditions, including the effects of a resveratrol dimer in focal cerebral ischaemia of rats (He et al, ; Poteet et al, ; Herrera‐Mundo and Sitges, ). Furthermore, emerging evidence suggests that different interventions improving overall health, especially cardiovascular health, may be undertaken to prevent or delay brain dysfunction effectively that might be associated with neuronal damage (Haan and Wallace, ; Nash and Fillit, ).…”
mentioning
confidence: 94%